Assessment of the willingness to avail of joint and bone health and wellness outpatient services at Medical Center Paranaque among senior citizens in Paranaque City - Manlulu, Elizabeth Edralin
Joint and bone diseases are associated with chronic and progressive intermittent pain throughout the ageing process. Joint and bone health and wellness involves promotive and preventive strategies that lessen the onset of metabolic diseases. Using a survey questionnaire, the present study described characteristics of 84 senior citizen respondents and determined whether they were willing to avail or not of joint and bone health and wellness services at he MCP-OPD. Majority of them reported themselves to be poor overall health status. Most of them have good healt-seeking behavior and means of access to health care services. They reported acute and chronic body pains and most of them had limitations in performing daily activities as a result of their body pains. There is unmet and urgent need for joint and bone health and wellness services among the respondents and majority of them were willing to avail of joint and bone health and wellness packages at the MCP-OPD. Although half of the respondents have had patient experince with minimal level of satisfaction at the MCP-OPD, majority of them will still avail of joint and bone health and wellness services at the MCP-OPD. Awareness regarding the presence of joint and bone and health and wellness packaged services at the MCP-OPD at present is a significantly associated with their willingness to avail the services at the same facility. The location of MCP-OPD and its affordable price offerings are its topmost qualities.